2010
DOI: 10.1089/pho.2008.2353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Surgery and CO2Laser on Intraoral Soft Tissue Pathologies and Evaluation of the Collateral Thermal Damage

Abstract: CO(2) laser is an effective instrument for soft tissue excisional biopsies with minimal intraoperative and postoperative complications and good pain control. CO(2) laser applications are suggested as an alternative method to conventional surgery on oral soft tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 22 publications
2
42
0
4
Order By: Relevance
“…This hemostasis may account for the minimal fluid extravasation observed, with a minimal inflammatory response around the tissues under surgical management. There was no need for sutures in all the cases because of the formed coagulated layer over the raw area with no evident bleeding, and to avoid the primary intention healing and reattachment [12,14]. In this clinical work, all patients were satisfied with good acceptance with respect to patient perceptions after laser and conventional surgical frenectomy and suggested that laser surgical frenectomy was superior to the conventional technique regarding patient perception and postsurgical discomfort.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This hemostasis may account for the minimal fluid extravasation observed, with a minimal inflammatory response around the tissues under surgical management. There was no need for sutures in all the cases because of the formed coagulated layer over the raw area with no evident bleeding, and to avoid the primary intention healing and reattachment [12,14]. In this clinical work, all patients were satisfied with good acceptance with respect to patient perceptions after laser and conventional surgical frenectomy and suggested that laser surgical frenectomy was superior to the conventional technique regarding patient perception and postsurgical discomfort.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, all patients returned to their normal day activities because of diminution of surgery time, depletion of blood loss and pain besides that patients were provided with minimally invasive surgery, where tissue injury is reduced to a minimal degree [3][4][5]16]. In this study, there was no post-surgical edema, because of laser-induced hemostasis and reduced tissue injury, except in three patients who had a mild edema that subsided after three days because of a relatively larger raw area, resulting in a more inflammatory response [12,17,18], since it is the result of a reduced swelling and a minimal inflammatory response and this can be explained by precision surgical laser procedures without any adverse effect on surrounding normal tissue, and the ability of lasers to seal lymphatic channels results reduced postoperative edema, which in turn results in less postoperative discomfort, also the sealing of nerve endings resulting in reduced inflammatory response, and the formation of a fibrin clot over the surgical wound that protects the wound from external irritation, causing less pain after surgery and avoiding the use of analgesic drugs [11]. Patients treated with laser surgery have no functional complications since there was no damage to adjacent healthy tissues, with less wound contraction during healing; meaning that there is less mucosal scarring, resulting in satisfactory mobility of the soft tissue and consequently, there is a minimal oral dysfunction [13,14,18,19].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Eversole (17) reported that after 6-years experience in soft tissue surgery with laser, the Er,Cr:YSGG system is comparable to conventional scalpel when it comes to histological evaluation, whereas CO 2 and Nd:YAG lasers create cytological artifacts, such as hyperchromatism, pleomorphism and nuclear elongation, that can cause diagnostic confusion. Conversely, other authors (18)(19)(20) stated that when employing the CO 2 laser it is hardly possible to make enough artifacts to invalidate the histological examination, if the laser is not deliberately misused. Both authors agree on the importance of the emission parameters to minimize thermal damage and occurrence of artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…In the following decade, especially CW and long-pulsed medical CO 2 lasers were tested for cutting mineralized tissue. CO 2 -laser wavelengths had already shown promising results for successful soft tissue treatment and thus helped establish the demand for laser osteotomy 32,33. However, the pioneering studies of Horch et al34,35 revealed serious biological complications with severe carbonization effects and a delayed bone healing compared with conventional mechanical osteotomies.…”
Section: Historical Background Of Laser-assisted Bone Cuttingmentioning
confidence: 99%